Prosodic Analysis of Pupuh Pucung using Mbrola Speech Synthesis Application - I Gusti Agung Indrawan; I Putu Eka Giri Gunawan (IJISTECH (International Journal of Information System and Technology), 2022)
Pupuh Pucung is one part of the sekar alit which is part of the Balinese song. Sekar alit/pupuh has a rule in writing lyrics called padalingsa, which consists of guru wilangan, namely the number of syllables in each line, guru dingdong, which is the vowel in the last word of each line and guru gatra, which is the number of lines in one stanza. This study discusses how the text-to-speech application can help in developing pupuh pucung. Text to speech is an application that converts text into sound. In this research, an application design that can sing Pupuh Pucung's lyrics was developed with the concept of text to sing. This study uses the mbrola application as a text-to-speech converter. The analysis results, namely the frequency of the fundamental tone, aim to determine each phoneme's initial frequency in Pupuh Pucung. With the initial frequency, it will shorten the range of subsequent prosodic observations. The use of pupuh pucung's fundamental tone as a guide for the formation of prosody can be used as an initial guide in forming pupuh pucung's prosody.